Knowledge, attitude, and practice of Bangladeshi residents during COVID-19 pandemic. - Mili Saha; Goutam Saha; Mynul Islam (Public Library of Science (PLoS), 2022)
Bangladeshi government has adopted some special steps to control the quick spread of the COVID-19 pandemic situation. However, the residents' knowledge, attitudes, and practices towards the disease directly impact the success of the controlling measures taken by the state. This article explores knowledge (K) about preventions, attitude (A) to the disease, and practices (P) of preventing the COVID-19 infection risks of different age groups residing in Bangladesh. Quantitative data were collected online using a KAP questionnaire from 932 participants. Also, statistical t and F tests have been used and analyzed and p-value, 95% Confidence Interval, Odd Ratio (OR), KAP scores, and multiple logistic regression analysis, are presented in this research. Results show the population is generally aware of the symptoms and social distancing. They are concerned about re-spreading and positive about staying home. The most significant findings of the study reveal that the old age group (age 50 or over) is the most alert group, male population are the most vulnerable with less care, people living outside Dhaka take less care and fewer preventive measures against the deadly virus, the young age group (age 18-25) is most optimistic while the female respondent group is best prepared among all the participants.